PERWUJUDAN HISTORIS SEBAGAI REPERTOIRE DALAM TENGGELAMNYA KAPAL VAN DER WIJCK KAJIAN ESTETIKA WOLFGANG ISER - Daratullaila Nasri (Balai Bahasa Kalimantan Barat, 2020)
This paper reviews historical materialization as repertoire in Hamka's Tenggelamnya Kapal van der Wijck novel. Repertoire is a concept attached to a theory of aesthetic response by Wolfgang Iser. Repetoire is a collection of knowledge owned by authors, consisting cultural elements (history, social, culture). Research method focused on aesthetic response which is about reading strategy and the interaction between text and its reader. It resulted in historical materialization in the form of background and foreground.